Seed Bank Gulma Pada Beberapa Kedalaman Tanah Tegakan Jambu Mete di Lahan Kering - Ngawit, I Ketut; Wangiyana, Wayan; Farida, Nihla (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
The dynamics of weed invasion in cashew guava is influenced by the potential of the standing soil as a weed seed bank. Therefore, research was carried out which aimed to examine weed species that had not yet grown because environmental factors were not yet supportive. The first research used a descriptive method and collected data in the field using an exploratory survey method. The second research used an experimental method, by observing the potential of various soil depths of cashew stands as a weed seed bank. The research results showed that 17 weed families were found in cashew plantations, consisting of 2 Ciperaceae species, 9 Poaceae species and 21 broadleaf species. The highest diversity, population and ability to grow simultaneously Weed bank seed occurs at a soil depth of 0 ± 30 cm, then decreases at a soil depth of > 30 ± 40 cm and is very low at a soil depth of > 40 ± 50 cm. Seed bank weed species which are always dominant at various soil depths are dominated by poaceae and broad-leaf weeds so that the number of species, the percentage that grows and the dry biomass weight is significantly higher than that of sedge weeds. The size of the seed bank is determined by the combination of seeds produced by previously growing weeds. So weed seeds will remain a problem as long as there is a supplier for these seeds.